Putting Services and Foreign Direct Investment with Endogenous Productivity Effects in Computable General Equilibrium Models - Tarr, David G. (World Bank, Washington, DC, 2014)
With the growing importance of services and foreign direct investment in services, it is important to have a framework to analyze the impact of the liberalization of barriers to foreign direct investment in services. This paper summarizes several recent papers and builds policy-based computable general equilibrium models showing the dynamics of services, foreign direct investment and the endogenous productivity effect from services. The modeling framework shows that the liberalization of barriers against foreign direct investment in services yields welfare gains several times larger than the usual estimates from traditional computable general equilibrium models, which focus on goods trade, not foreign direct investment in services. The larger estimates are consistent with econometric evidence on the gains from services liberalization. The paper begins with a small stylized model to help understand the fundamental economics. Then it describes models developed at the request of the Russian government to assess the potential impact of Russia's accession to the WTO. Reviews of the work indicated that the modeling helped the Russian government gain public support for the WTO entry. The paper also describes a new technique that allows modelers to include tens of thousands of households in the model.